1987
DOI: 10.1530/jrf.0.0800105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic intravenous infusion of PGF-2  and 13,14-dihydro-15-keto-PGF-2  on the release of oxytocin-associated neurophysin from the ovary in the ewe

Abstract: Summary. Systemic intravenous infusion of physiological concentrations of PGF-2\g=a\ and its major metabolite, 13,14-dihydro-15-keto-PGF-2\g=a\(PGFM) into non-pregnant ewes possessing a corpus luteum induced the release of oxytocin\p=m-\neurophysin.These results suggest that, during luteolysis, endogenous release of uterine PGF-2\g=a\would be able to stimulate the release of ovarian oxytocin and oxytocin\p=m-\neurophysinfrom the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The finding that exogenous PGF-2u will cause release of oxytocin (Flint 8c Sheldrick, 1982;Lamsa et ai, 1989) and measurement of concomitant pulses of PGF-2a and oxytocin during luteo¬ lysis (Fairclough et ai, 1980(Fairclough et ai, ,1983Flint & Sheldrick, 1983;Vighio & Liptrap, 1986) led Flint et ai (1986) to conclude that an essential aspect of luteal regression was participation by oxytocin and PGF-2a in a positive feedback loop. An infusion of PGFM caused release of oxytocin-associated neurophysin from CL in cyclic ewes (Watkins & Moore, 1987). Addition of oxytocin to uterine endometrium collected from post-partum cows resulted in the release of PGFM in vitro (Del Vecchio et ai, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that exogenous PGF-2u will cause release of oxytocin (Flint 8c Sheldrick, 1982;Lamsa et ai, 1989) and measurement of concomitant pulses of PGF-2a and oxytocin during luteo¬ lysis (Fairclough et ai, 1980(Fairclough et ai, ,1983Flint & Sheldrick, 1983;Vighio & Liptrap, 1986) led Flint et ai (1986) to conclude that an essential aspect of luteal regression was participation by oxytocin and PGF-2a in a positive feedback loop. An infusion of PGFM caused release of oxytocin-associated neurophysin from CL in cyclic ewes (Watkins & Moore, 1987). Addition of oxytocin to uterine endometrium collected from post-partum cows resulted in the release of PGFM in vitro (Del Vecchio et ai, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin is thought to participate along with PGF, in a positive feedback loop that propagates the signal for luteolysis [34,35]. Although release of oxytocin-induced PGF 2 a has not been associated with initiation of functional regression, whether or not oxytocin initiates internucleosomal fragmentation has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kehl and Carlson (1981), l3, 14-dihydro-PGF2α caused premature luteal regression in rabbits. Watkins and Moore (1987) suggested that PG metabolites (PGMs) cause the release of oxytocin from the CL and lead to continuation of luteolytic activity. In the same context, PGF2α…”
Section: Serum Sexual Hormones Concentrationmentioning
confidence: 99%